Outcome Studies in the Field of Pastoral Counselling: A Focused Review of Research Published between 1990 and 2020 - SIPOS, Zsolt; TÖRÖK, Gábor Pál; JÁKI-SZABÓ, Zsuzsanna; BÓNÉ, Veronika (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2025)
This literature review examines the empirical evidence of the impact of pastoral care, focusing on the areas that have been studied in terms of measurable and verifiable outcomes. By analysing 34 international studies published between 1990 and 2020, we assessed the methodological diversity and empirical depth of research in this field. The review encompasses qualitative, quantitative, and mixed-method studies alike, including small- and large-sample investigations. Our findings suggest that while the impact of pastoral counselling is empirically measurable and verifiable, significant methodological limitations persist, particularly regarding measurement precision and the identification of influencing factors. Compared to psychotherapies integrating religiosity and spirituality, pastoral care research is less extensive and often based on smaller, less differentiated samples, with limited attention to the professional competence levels of care providers. Most outcome studies have been conducted in hospital contexts involving patients with physical or mental health conditions and their relatives. Results highlight the need for further empirical work using more rigorous and diversified methodological approaches, broader research settings, and assessment tools adapted to the qualification level of pastoral care providers, in order to establish a more comprehensive and evidence-based understanding of pastoral care effectiveness.